1991
DOI: 10.1159/000163620
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Esophageal Carcinoma Cell Line Established on Confluent Monolayer, and Advantage of Confluent Monolayer Surface Structure for Attachment and Growth

Abstract: Biopsy tissue from a 72-year-old Japanese woman with metastasis to the cervical lymph nodes of recurrent esophageal carcinoma was adapted for culturing on the surface of lethally X-irradiated confluent monolayers of Balb/c 3T3 cells, and a continuous-growing tumor cell line was developed. These cells were found to contain keratinous material by immunohistochemical staining. We confirmed that these cells were of human origin by performing chromosome analysis. Thus, this line, designated as KSE-2 line, was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…KSE-1 and KSE-2, which were established cell lines derived from two patients with oesophageal squamous cell carcinoma in our department, were used in this study (Matsuoka et al 1987(Matsuoka et al , 1991. These cell lines were routinely cultured in monolayers on plastic dishes using Dulbecco's modified Eagle's medium (DMEM) (Nissui Co., Japan) supplemented with 10% fetal calf serum (Difco Laboratories, USA) and 100 pg/ml of gentamicin (Essex Co., Japan).…”
Section: Cellsmentioning
confidence: 99%
“…KSE-1 and KSE-2, which were established cell lines derived from two patients with oesophageal squamous cell carcinoma in our department, were used in this study (Matsuoka et al 1987(Matsuoka et al , 1991. These cell lines were routinely cultured in monolayers on plastic dishes using Dulbecco's modified Eagle's medium (DMEM) (Nissui Co., Japan) supplemented with 10% fetal calf serum (Difco Laboratories, USA) and 100 pg/ml of gentamicin (Essex Co., Japan).…”
Section: Cellsmentioning
confidence: 99%
“…We have previously found that both CSPs and CSPs fixed with 3% glutaraldehyde (F-CSPs) provide a favorable substratum for the attachment and proliferation of malignant cells (8,10). In the present study, we investigated the growth of early" passage human fibroblasts, normal cell lines, and neoplastic cells on FCSPs.…”
Section: Introductionmentioning
confidence: 96%